Micro-spatial and seasonal distributions of two sympatric host races of the phytophagous ladybird beetle Henosepilachna diekei (Coleoptera: Coccinellidae) and their host plants in West Java, Indonesia - Kei W Matsubayashi; Sih Kahono; Sri Hartini; Hauro Katakura (Treubia, 2013)
Divergent adaptation to different host plants may promote reproductive isolation between hostspecific populations in phytophagous insects, since strict preferences for different host plants act as an isolating barrier between populations on the different hosts. Moreover, a high dependence on the host plants may cause additional reproductive barriers, e.g., differences in micro-spatial distribution and phenology between host-specific populations when the host plants differ in these characters. However, few studies have specifically addressed these two types of host-plant-induced isolating barriers. Here we compared the microspatialdistribution and seasonal fluctuation of two host races of theÂ phytophagous ladybird beetle Henosepilachna diekei (Coleoptera: Coccinellidae: Epilachnine) in Bogor, West Java, one depending on Mikania micrantha (Asteraceae) and the other on Leucas lavandulifolia (Lamiaceae). In the field, M. micrantha was far more abundant and common than L. lavandulifolia throughout the year. M. micrantha was found in relatively moist habitats with moderate sunlight, while L. lavandulifolia was found in dry, sunny, open habitats. Consequently, the beetles depending on M. micrantha were more common and abundant than those depending on L. lavandulifolia. Although the two host races could encounter one another where the two host plants occurred in close proximity, they infrequently did so because of strict host fidelity coupled with differences in the abundance and habitat of the two host plants. On the other hand, we detected no evidence of host-related seasonal isolation between the two host races.